Forward converters for dual voltage switched reluctance motor drives. - Barnes, M.
A new circuit is presented which allows a switched reluctance motor to operate from AC mains or a low voltage battery supply. In addition the AC mains can be used to charge the battery. The switched reluctance motor is used as the voltage-changing transformer, potentially reducing the cost of the system. The operation of the drive is explained, and results of an experimental prototype are presented
Keywords: AC mains supply; Battery charging; Cost reduction; Dual voltage switched reluctance motor drives; Forward converters; Low voltage battery supply; Voltage-changing transformer